Effect of short‐term low molecular weight heparin on patency following successful salvage of arteriovenous access with recurrent thrombosis. Issue 4 (25th November 2020) - Tan, Ru Yu; Pang, Suh Chien; Tng, Alvin Ren Kwang; Ng, Heng Joo; Teh, Swee Ping; Tan, Seck Guan; Tang, Tjun Yip; Foo, Marjorie Wai Yin; Gogna, Apoorva; Chong, Tze Tec; Tan, Chieh Suai
Abstract: Aim: This study aims to investigate the effect of low molecular weight heparin (LMWH) in maintaining the patency of arteriovenous (AV) access with recurrent thrombosis. Methods: Following successful thrombectomy, 66 patients with recurrent thrombosis were included in the study. The primary, assisted primary and secondary patency rates of patients who received LMWH (n = 24) were compared with those who did not receive anticoagulant (n = 42) using Kaplan‐Meier analysis. Cox‐regression analysis was performed to investigate potential predictors of patency rates. Results: The mean dose of enoxaparin used was 40 ± 13.1 mg or 0.74 ± 0.2 mg/kg daily for a median duration of 14 (IQR 7, 28) days. The mean trough anti‐Xa concentrations measured after two doses of LMWH was 0.17 ± 0.13 IU/mL. Kaplan‐Meier analyses for mean primary, assisted primary and secondary patency rates of LMWH vs no anticoagulation groups were 149 (95% CI: 91 ‐ 207) vs 87 (95% CI: 42‐132) days ( P  < .006), 230 (95% CI: 142‐320) vs 107 (95% CI: 62‐150) days ( P = .01) and 438 (299‐579) vs 294 (95% CI: 197‐392) days ( P = .08) respectively. LMWH remained a significant protective predictor of primary (HR: 0.49; 95% CI: 0.25‐0.86; P = .02) and assisted primary patency rates (HR: 0.51; 95% CI: 0.27‐0.98; P = .04) after adjusting for patient age, access age, type of AV access, presence of peripheral vascular disease and haemoglobin levels. Conclusion: LMWH may improve short and mid‐term patency rates for AV accesses with recurrent thrombosis. SUMMARY AT A GLANCE: This study showed that low molecular weight heparin (LMWH) may improve short and mid‐term patency rates for AV accesses with recurrent thrombosis.